2013
DOI: 10.1111/cpr.12011
|View full text |Cite
|
Sign up to set email alerts
|

Metaphase arrest and delay in cell cycle kinetics of root apical meristems and mouse bone marrow cells treated with leaf aqueous extract of Clerodendrum viscosum Vent

Abstract: It may be said that LAECV contains mitostatic and metaphase arresting components that are able to induce significant metaphase arrest in root apical meristems and also in mouse bone marrow cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
57
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(62 citation statements)
references
References 27 publications
5
57
0
Order By: Relevance
“…Such a reduction in mitotic index suggests that exposure to AESN led to the cell cycle disturbances and decrease in cell number entering mitotic division. In the present and our previous study, onion root apical meristem cells were found to be excellent cell system for cell cycle kinetics analysis [26] . Levan first introduced A. cepa root tip assay and later it was used as a standard method to study genotoxicity [33][34][35][36][37][38] .…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…Such a reduction in mitotic index suggests that exposure to AESN led to the cell cycle disturbances and decrease in cell number entering mitotic division. In the present and our previous study, onion root apical meristem cells were found to be excellent cell system for cell cycle kinetics analysis [26] . Levan first introduced A. cepa root tip assay and later it was used as a standard method to study genotoxicity [33][34][35][36][37][38] .…”
Section: Discussionsupporting
confidence: 55%
“…In green gram seedlings, the root growth retardation increased from 2 to 77% for the increased concentration from 0.5 to 6 mg/ml (p<0.001). Our previous study showed colchicine, a metaphase arresting agent, also induced growth retardation in green-gram seedlings in a dose dependent manner [26] . The .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The reduction in mitotic index might be explained as hindrance before the onset of prophase, the arrest of one or more mitotic phases or slowing down the cell cycle progression during mitosis. Studies on Allium root tip cells and mouse bone narrow cells exhibit decreased mitotic activity with Clerodendrum extracts 28 . The antimitotic activity of root tip cells was exhibited by a number of plant extracts 29,30 .…”
Section: Discussionmentioning
confidence: 99%